2016
DOI: 10.1242/jeb.137166
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic scope increases throughout an ecologically relevant temperature range in coho salmon

Abstract: Aerobic scope (AS) has been proposed as a functional measurement that can be used to make predictions about the thermal niche of aquatic ectotherms and hence potential fitness outcomes under future warming scenarios. Some salmonid species and populations, for example, have been reported to exhibit different thermal profiles for their AS curves such that AS peaks around the modal river temperature encountered during the upriver spawning migration, suggesting species-and population-level adaptations to river tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 79 publications
3
24
0
Order By: Relevance
“…; Raby et al. ). Characteristics of catch‐and‐release angling episodes, such as air exposure, fight duration, and water temperature, can cause unrecoverable physiological disruptions (Cooke et al.…”
mentioning
confidence: 97%
“…; Raby et al. ). Characteristics of catch‐and‐release angling episodes, such as air exposure, fight duration, and water temperature, can cause unrecoverable physiological disruptions (Cooke et al.…”
mentioning
confidence: 97%
“…Several studies in juvenile salmonids have yielded similar results to that of and Raby et al (2016). In juvenile coho salmon from the Seymour River hatchery in BC, Casselman et al (2012) found that aerobic scope was maintained or even continued to increase slightly across ecologically relevant temperature ranges.…”
Section: Routine and Maximum Metabolic Ratessupporting
confidence: 55%
“…Clark et al (2011) found that aerobic scope in adult pink salmon (O. gorbuscha) continued to increase at temperatures higher than the fish would have experienced at any point in their life cycle, peaking at 21 ºC and only starting to decline at approximately 23 ºC. Another study done by Raby et al (2016) testing aerobic scope in adult coho salmon also found that performance was maintained across ecologically relevant temperatures, those that the fish were likely to encounter at any point in their life cycle.…”
Section: Routine and Maximum Metabolic Ratesmentioning
confidence: 97%
“…Zhang and Gilbert cite a few studies where this may be the case, but they fail to acknowledge recent literature, including an extensive meta‐analysis, which finds that in most fish species normalO2,max increases over most of the measured temperature range, showing no or only a minor decline as lethal temperatures are approached (Clark et al ., 2013 a , b ; Jutfelt et al ., ; Norin et al ., ; Lefevre, ). Indeed, we encourage Zhang and Gilbert to focus on ecologically‐relevant temperatures when examining these concepts (Clark et al ., ; Raby et al ., ). To counter more of Zhang and Gilbert's concerns, the meta‐analysis also finds little evidence for differences in the shape of the thermal performance curve for both normalO2,max and aerobic scope in acclimated v .…”
Section: Slopes (In µMol O2 L−1 Min−1) For the Decrease In Water Oxygmentioning
confidence: 97%